Nie-Piękno w języku i kulturze: łamanie zasad grzeczności językowej w tekstach utworów zespołu Nocny Kochanek jako strategia humorystyczna = Non-Beauty in language and culture: breaking the rules of language politeness in the lyrics of the songs of the band Nocny Kochanek as a humorous strategy - Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to analyse the instances of violation of language politeness rules in the lyrics of Nocny Kochanek, a Polish heavy metal band, and to determine the aim of such a communication strategy. The analysis comprised thirty-four sets of lyrics in which the following instances of the violation of the rules of language politeness were identified: taboo topics, negative attitudes towards the partner, failure to comply with Grice?s conversational implicatures and linguistic errors.
Keywords: grzeczność językowa; tabu; strategia nadawcza; Nocny Kochanek (zespół muzyczny); implikatury konwersacyjne Grice`a; language politeness; taboo; communication strategy; Grice`s conversational implicatures